PERFORMANCE MANAGEMENT AND EMPLOYEE PRODUCTIVITY IN SELECTED LARGE ORGANIZATIONS IN SOUTH-EAST, NIGERIA - OKEKE,M. N.,; ONYEKWELU, N. P.,; AKPUA, J.,; DUNKWU C., (IJRDO - Journal of Business Management, 2019)
The study examinedthe effect of performance management on employee productivity using selected large organizations in South East, Nigeria. Specifically the study examined the extent to which 360 degree feedback appraisal, performance evaluation, self-assessment and performance review influence employee productivity. Relevant theoretical and empirical literatures were reviewed. The study was anchored on Equity Theory. Descriptive survey research design was adopted in this study. The population of the study was 2081 and the sample size was 366 using Taro-Yamane’s formula. Simple percentages, descriptive statistics, and Multiple Regression Analysis (MRA) were used in testing the hypotheses. Findings from the analysis showed that 360 degree feedback appraisal had a significant influence on employee productivity, performance evaluation had a significant effect on employee productivity, Self-assessment had no significant influence on employee productivity and performance review had a significant effect on employee productivity. Based on the findings, the study concluded that performance management has significant effect on employee productivity in the Nigeria banking industry. The study recommended that organizations should lay emphasis on 360 degree feedback appraisal since it was found to have significant relationship with employee productivity.Performance evaluation should be based on job description given to the employees. Organizations should pay adequate attention, monitor and lay emphases on self-assessment system in order to improve employee productivity.